Wideband Spectrum-Sliced ASE Source Operating at 1900-nm Region Based on a Double-Clad Ytterbium-Sensitized Thulium-Doped Fiber - Halder, Arindam; Paul, Mukul Chandra; Shahabuddin, Nurul Shahrizan; Harun, Sulaiman Wadi; Saidin, Norazlina; Damanhuri, Siti Sarah Ahmad; Ahmad, Harith; Das, Shyamal; Pal, Mrinmay; Bhadra, Shyamal Kumar (Institute of Electrical and Electronics Engineers (IEEE), 2012)
A wideband spectrum-sliced amplified spontaneous emission (ASE) source operating in 1900-nm region is demonstrated using a newly developed double-clad ytterbium-sensitized thulium-doped fiber (YTF) and a Sagnac loop mirror. The YTF used was drawn from a D-shape preform, which was fabricated using the modified chemical vapor deposition (MCVD) and solution doping technique. The YTF was pumped by a 980-nm multimode laser to generate an ASE at 1900 nm through the transition of thulium ion from 3F 4 to 3H 6 with the assistance of ytterbium to thulium ion energy transfer. The broadband ASE was spectral sliced by the loop mirror, which was constructed using a 3-dB coupler and a piece of polarization maintaining fiber (PMF). A wideband comb with channel spacing of 3.3 nm and an extinction ratio of 9 dB was achieved with a multimode pump power of 1 W within a wavelength range of more than 300 nm. The center of the comb spectrum was at 1888 nm with peak power of around -53 dBm.